EFEK TRANSPARANSI KEUANGAN, GAYA KEPEMIMPINN, LINGKUNGAN KERJA, DAN INSENTIF TERHADAP KEPUASAN KERJA DI ALFAMIDI MALENGKERI - Zulkarnain Basir (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to determine the effect of financial transparency, leadership style, work environment, and incentives on employee job satisfaction Alfamidi Malengkeri. Quantitative research method with primary and secondary data sources, primary data obtained using questionnaires that have been tested for validity and reliability, data analysis used is classical assumption test, hypothesis test with multiple linear regression using SPSS 20.00 program. The results showed that financial transparency had a positive and significant effect on job satisfaction. The second test, leadership style has a positive and significant effect on job satisfaction. The third test, the work environment has a positive and significant effect on job satisfaction. The fourth test, incentives have a positive and significant effect on job satisfaction. So that simultaneously financial transparency, leadership style, work environment and incentives have a positive and significant effect on employee job satisfaction at Alfamidi Malengkeri.